P2X7, inflammation and gastrointestinal disease - Stevenson, Diane J. (2008)
The inflammatory bowel diseases, ulcerative colitis and Crohn's disease are characterised by spontaneously relapsing and remitting inflammation, associated with increased mucosal levels of the inflammatory cytokine, interleukin-1 (IL-1)β. IL-1β processing and release is mediated by ATP stimulation of the purine receptor, P2X7. P2X7 is a membrane ion channel highly expressed in immune cells. Signal transduction occurs via rapid cation exchange, plasma membrane depolarisation and increased intracellular calcium. Additionally, prolonged or repeated P2X7 stimulation leads to formation of a non-selective membrane pore permeable to small molecules, and ultimately to cell death.